Manajemen Sumber Daya Manusia dalam Persfektif Hadits - Rifa Zakiah Mahmudah; Mulyawan Safwandi Nugraha (Universitas Katolik Widya Karya Malang, 2023)
As prospective managers of Islamic educational institutions we must know the hadith relating to management itself. The method used is a qualitative approach. The data collection technique used in this research is library research. The results and discussion of this article are this is related to human resource management in perfect Islam. The review of hadith can be interpreted as a process of managing and realizing human and Muslim society to truly believe in and fear Allah and are expected to be able to carry out full responsibility duties, reproduce scholars who have Islamic qualities , faith, knowledge, and noble character for the sake of building himself and his society seen from the perspective of the hadith of the Prophet Adapu the conclusion of this article is Management of the Prophet Muhammad and Khulafaurrasyiddin Management of human resources at the time of the Prophet placed a person seen from being able or not knya completed a mandate given especially in the field of management. That he put the right person in the right position or